Manifestasi Dakwah Bil-hal dalam Pengelolaan Sampah - Fikri Dina Intan (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2024)
Da'wah bil-hal should be manifested in waste management, but in reality it often does not materialize because it is trapped in the community's knowledge about da'wah contained in waste management activities. This study intends to analyze the manifestation of da'wah bil-hal of the BESTARI Waste Bank Community in waste management in Tegal Regency. This study uses a qualitative method with a social approach, where data is obtained through structured interviews, structured observations, and documentation. The BESTARI Waste Bank Community contributed as the main informant in this study.The results of the study indicate that the manifestation of da'wah bil-hal of the BESTARI Waste Bank Community is reflected in waste management activities in the application of Islamic law in the 3R principle (Reduce, Reuse and Recycle), the formation of strong Muslim characters, and environmental initiatives through waste banks.